Fast Moving Consumer Goods Industry in Rural Market of India: A Case of Mutual Reinvigoration - Kumar, Brajesh; Gogoi, Mintu (Ushus Journal of Business Management, 2021)
The present study has been undertaken to make an assessment of the growing eminence of FMCG industry in the era of enriching rural market in India. The Indian Fast Moving Consumer Goods (FMCG) industry began to take shape during the past five decades. The FMCG sector is a keystone of the Indian economy as it touches every aspect of human life. The FMCG sector, which offers tremendous growth prospects, are food and beverage sector, health care and personal care. Presently, rural India accounts for 34% of total FMCG consumption, but it accounts for more than 40% consumption in major FMCG categories like as personal care, hot beverages, and fabric care. Moreover, 80% of FMCG categories are growing faster in rural India as against urban India (Nielson, 2011). There is a huge growth potential for all the FMCG companies as the per capita consumption of almost all products in the country is amongst the lowest in the world. In recent years, rural markets have acquired significance in countries like China and India, as the overall growth of the economy has resulted in substantial increase in the purchasing power of the rural communities. On account of the green revolution in India, the rural areas are consuming a large quantity of industrial and urban manufactured products.